UTILIZATION OF DIGITALIZATION FOR MSME DEVELOPMENT AS A PILLAR OF ECONOMIC DEVELOPMENT - Diwayana Putri Nasution; Hilmi; Rizki Ramadhan; Feri Susilawati; Rachmad Ikhsan; Lia Nazliana Nasution; Wahyu Indah Sari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The purpose of this study is to see the use of MSME digitalization to develop MSMEs as a pillar of economic development. Digitalization is very necessary in the global era, where human resources are required to be able to adapt to the development of digitalization. However, in reality, this has not happened comprehensively in various aspects of MSMEs. The reason behind this research is that many MSMEs still do not have adequate capabilities in terms of digitalization. The research method used is the literature review method and digitalization theory which explains the use of digitalization for the development of MSMEs. The results of the study show that the use of digitalization is very influential in increasing the competitiveness of MSMEs and their development. MSMEs also contribute optimally to economic development. The suggestion from this study is that training and development of digitalization capabilities are needed in an effort to increase the development of MSMEs as a pillar of Indonesia's development.